Geomechanically Modeling for Wellbore Stability Analysis: A Literature Review - Rasyid, Aly; Hendarmawan, Hendarmawan; Haryanto, Agus Didit; Endyana, Cipta (International Journal of Innovative Research and Scientific Studies, 2025)
Wellbore stability is a critical aspect of drilling operations, directly impacting the safety, efficiency, and cost-effectiveness of resource extraction and subsurface engineering projects. A comprehensive geomechanically model is essential for predicting and mitigating wellbore instability, encompassing the in-situ stress state, rock strength, and the interaction between drilling fluid and the surrounding rock formation. This review synthesizes the current literature on geomechanically modelling techniques for wellbore stability analysis, highlighting the evolution of methodologies, key parameters influencing stability, and the application of these models in both conventional and unconventional reservoirs. Additionally, the review addresses the challenges associated with model calibration and validation, emphasizing the importance of integrating well logs, core data, and field observations to enhance predictive accuracy and optimize drilling practices. Real-time monitoring systems and probabilistic decision algorithms further enhance wellbore stability management by enabling dynamic adjustments to drilling parameters and trajectories. Furthermore, this review identifies gaps in current research and proposes future directions for advancing geomechanically modelling to address the complexities of subsurface environments and improve the overall performance of drilling operations.